Awareness of Medical Mask Waste Management for Young People on Central Java and Special Region of Yogyakarta Provinces During the Covid-19 Pandemic - Garnis Perwitasari, Iyualevi; Saniscara Nugraheni, Rachel; Nur Fadilah, Rizky; Sagita Armadhan, Winda; Shafa Alfitra, Zhalzabilla; Hawali Abdul Matin, Hashfi; Rachmawati, Siti (Diponegoro University, 2023)
The Covid 19 pandemic that hit Indonesia caused the problem of increasing medical mask waste. Medical masks are included in B3 waste because they are infectious. Therefore, special treatment is needed to mask waste, so it doesn't transmit disease. This study was conducted to determine the awareness of medical mask waste management in young people, especially those who live in the provinces of Central Java and the Special Region of Yogyakarta. The research was conducted by distributing questionnaires to respondents aged 17-24 years. This research used descriptive analysis with a quantitative approach. Based on the results of the study, it is known that most of them already know the meaning of B3 waste, where 65% of respondents can answer questions correctly about the type of waste and about 95% of respondents considered medical mask waste to be harmful to the surrounding environment. Based on the results of data analysis, it is known that the respondents have shown awareness of the dangers of mask waste, but from the results of the questionnaire, it is also known that the respondents do not have the awareness to process waste. From the 151 respondents, there were only 4 people who did the processing. So that it can be seen that the level of awareness of medical waste management in young people, especially those who live in the Province of Central Java and the Special Region of Yogyakarta is still very low. The results of the questionnaire also show that there are still few TPS specifically for hazardous waste around the settlements.